PALEOGENE CLIMATIC FLUCTUATIONS AND BIOTIC MIGRATIONS IN THE NORTH PACIFIC - Beniamovskii V.N.; Gladenkov Yu.B. (My University, 1996)
Analysis of the Paleogene planktonic foraminifers from the sections of Kamchatka, Koryak Highland, the North Pacific, and Japan revealed several age levels of the occurrences of warm-water (subtropical) assemblages: late Danian, late Thanetian-early Ypresian, early Lutetian, early Bartonian, and early Priabonian. Appearance of these assemblages at high latitudes can be attributed to climatic warmings that led to their long-distance (up to 2000 or 2500 km) migrations in the northern direction. Some past climatic fluctuations can be correlated with eustatic sea-level oscillations. A high rate of migrations and relatively short duration of warming phases in comparison with cooling phases are recorded.
Keywords: Paleogene; Cenozoic::Paleogene; Кайнозой::Палеоген